A Study of Profitability Performance of Public Sector Banks in India - Selvakumar, M.; Kathiravan, P. G. (Indian Journal of Finance, 2009)
Banking system is an important constituent of the overall economic system. It plays an important role in mobilizing the nation’s savings and in channelizing them into high investment priorities and better utilization of available resources. Hence, banking can better be described as the kingpin of the chariot of economic progress.Banking, if equated with money lending, is perhaps as old as the civilization itself. However, modern banking is something really different from mere lending. It is far more sophisticated and complicated. In a developing economy, the role of banks is more formative and purposeful than in the developed one. In a developing country, where the banking habits of the people are not developed, the task of creating and spreading the banking habits and of mobilizing the country’s resources becomes a challenging one. It is here that banks play a crucial role because they act as a bridge between those who require finance and those who have finance. Banks, thus, are an important instrument in making more efficient use of available savings.